Prevalence of Certain Urogenital Bacterial Mollicutes in Patients Suffering from Infertility - Motasem Y. Al-Masri; Intesar Khaleel Ashour; Ashraf Swafta; Sami Al-Shunar (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. Mollicutes urogenital tract infections are considered a possible cause of infertility worldwide. Genital Mollicutes infections are difficult and impractical to diagnose by culturing or serology. Mollicutes included in this study were Mycoplasma hominis, Ureaplasma urealyticum, and Mycoplasma genitalium. This cross-sectional study aimed to determine the prevalence of M. hominis, U. urealyticum, and M. genitalium genital infections among infertile males and females patients. Methods. This study included 103 patients who visited Al-Shunar Clinic in Nablus city in Palestine and diagnosed with infertility during January 2018 to October 2018. The semen, urine, and/or vaginal swab specimens collected from patients were examined by PCR for detection of M. hominis, U. urealyticum, and M. genitalium. Results. A total of 57 semen, 37 urine, and 16 vaginal swab specimens were collected. Out of the 110 examined specimens, 35 (31.8%) were PCR positive for at least one Mollicutes, which were 16 (14.6%) M. hominis, 11 (10%) U. urealyticum, and 8 (7.3%) M. genitalium. Significant association were found between infections of M. hominis and U. urealyticum (P=0.044) and between M. hominis and M. genitalium (P=0.005) infections. M. hominis infection was found in significantly (P=0.048) higher percentage in males (20.6%) in comparison with females (5.7%). On the other hand, M. genitalium infection rate in females (8.6%) was slightly higher than males (7.4%). M. hominis was more prevalent in all age groups except for patient’s age group 40–50 years old, where M. genitalium was more prevalent. M. hominis was also more prevalent in all occupation types and among all smokers. Conclusion. Urogenital infections caused by M. hominis, M. genitalium, and U. urealyticum could be a possible cause of infertility among patients with different age groups, genders, and occupations. Thus, more attention by infertility centers and physicians is required in adopting molecular methods for diagnosis of infections by these microorganisms.